Social Influence, Religiosity, and Salesperson Service on Saving Intention in Islamic Banks: The Mediating Role of Perceived Ease of Use of Technology - Aris Tri Haryanto; Fitri Wulandari (Shirkah: Journal of Economics and Business, 2022)
Research on the Theory of Planned Behavior (TPB) in the context of Islamic banks management has been conducted for years. However, studies investigating the mediating role of perceived ease of use of technology on saving intention in Islamic banks by considering social influence, religiosity, and salesperson service still require more paucity of evidence. This study adopted the TPB and Perceived Behavior Control (PBC). Purposive sampling was used to select 250 respondents who were customers of Islamic banks in Surakarta municipality, Indonesia. The data were analyzed by using the Structural Equation Model (SEM) with SPSS AMOS 22.  The results indicate that social influence, religiosity, and salesperson service have a positive and significant impact on saving intentions in Islamic banks. With partial mediating results, perceived ease of use of technology mediates the effect of social influences on saving intention in Islamic banks.  Meanwhile, the role of perceived ease of use of technology in mediating social influence on saving intentions is ineffective. Salesperson service has the biggest effect on saving intentions since they are directly interacting with customers. The results contribute to providing fruitful insights to sharia banks that sales person service and religiosity are two crucial factors determining the consumers’ satisfaction.